Investigation of a solid oxide fuel cells catalyst LaSrNiO4: Electronic structure, surface segregation, and oxygen adsorption. (14th December 2016) - Zhou, Yongjun; Lü, Zhe; Xu, Shifeng; Xu, Dan; Wei, Bo
Abstract: High-temperature tetragonal phase La2 NiO4 bulk and surface models have been constructed to investigate electronic structure, surface segregation and oxygen adsorption by first-principle calculations. The electronic structure of La2 NiO4 is calculated and compared with previous study. The correlation between the formation of oxygen vacancy and Sr segregation is studied for LaSrNiO4 (100) surface to explain the effect of Sr segregation on oxygen reduction reaction activity. The oxygen vacancy can be formed easily at non-Sr segregation LaSrNiO4 (LSNO) surface. The calculated results of segregation energy demonstrate that Sr atom easily segregates toward the surface and the oxygen vacancy suppresses the Sr surface segregation by lowering the Sr surface segregation energy. The adsorption mechanisms of oxygen molecule at LSNO (100) surface have also been studied. The hybridization between O 2p state and Ni 3d state indicates that Ni and O atoms are bonded together by NiO chemical bond. Highlights: The surface oxygen vacancy suppresses Sr surface segregation. La2 NiO4 exhibits a typical metallic character. The absolute values of O2 adsorption energies show a trend of Ni > O > La > Sr sites.